1983
DOI: 10.1086/131190
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of six Wolf-Rayet stars - The latest and faintest

Abstract: We present absolute spectrophotometry and classification of six relatively faint galactic Wolf-Ray et (WR) stars for which previous photometry was poor. One of these objects, the heavily reddened infrared source CRL 2179, is the faintest known galactic WR star, with a visual magnitude ~ 22. Its spectral type is WC10, later than that of any other known Population I WC star. Another faint star, WR 122, has a strong NII emission-line spectrum which is unprecedented: we define its type as WN10. The other four star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…The latter includes the data of Massey & Conti (1983) (V band), Cohen & Vogel (1978) (V band), Allen et al (1977) (JHKL bands), Williams et al (1987) Figures 3 and 4 also show the 2.13 µm visibility and SED of those 5 models, which proved to be best suited for the dust shell of WR 118 in the framework of spherical symmetry. Their parameters are given in Tables 1 and 2.…”
Section: Results Of Calculations and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The latter includes the data of Massey & Conti (1983) (V band), Cohen & Vogel (1978) (V band), Allen et al (1977) (JHKL bands), Williams et al (1987) Figures 3 and 4 also show the 2.13 µm visibility and SED of those 5 models, which proved to be best suited for the dust shell of WR 118 in the framework of spherical symmetry. Their parameters are given in Tables 1 and 2.…”
Section: Results Of Calculations and Discussionmentioning
confidence: 94%
“…It is classified as WC9-10 ( Allen et al 1977;Massey & Conti 1983). Its very prominent IR excess is attributed to the thermal emission of a warm carbon dust shell.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that previous studies have spectroscopically verified the presence of a WC9 star at the center of WR112 (Massey & Conti 1983;Figer et al 1997). Additionally, a binary companion is inferred from .…”
Section: On the Nature Of The Wr112 Nebula: Mass Loss From A Previoumentioning
confidence: 94%
“…Near-IR observations, however, are not sensitive to cooler dust that has propagated further from the central system. The late-type WC+OB binary WR112 (Massey & Conti 1983;van der Hucht 2001) is one of the few dusty WC systems whose nebula has been detected and resolved in the mid-infrared (8-18μm; Marchenko et al 2002. Others known are WR48a (Marchenko & Moffat 2007) and WR140 Williams et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered by Nassau & Stephenson (1963), who proposed a WR classification based on the strong emission-line spectrum. It was later reclassified as a late nitrogen-type WR (WN type) based on nitrogen emission-line ratios in the optical spectrum (Massey & Conti 1983), then later proposed to be a B [e], O[e], or Ofpe/WN9 star based on its optical-IR spectral properties (van der Hucht 1997). Subsequently, more detailed multi-wavelength investigation by Crowther & Smith (1999;hereafter CS99) showed that although NaSt1 is indeed a hot luminous object with L ∼ 10 5.1 -10 6.1 L⊙, its emission-line spectrum is mostly of nebular origin, not stellar.…”
Section: Introductionmentioning
confidence: 99%